2005
DOI: 10.1021/bi050598t
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Peptides Derived from Homologous Loop Regions in the Laminin α Chain LG4 Modules Interact with both α2β1 Integrin and Syndecan-2

Abstract: Laminin alpha chains show diverse biological functions in a chain-specific fashion. The laminin G-like modules (LG modules) of the laminin alpha chains consist of a 14-stranded beta-sheet sandwich structure with biologically active sequences found in the connecting loops. Previously, we reported that connecting loop regions between beta-strands E and F in the mouse laminin alpha chain LG4 modules exhibited chain-specific activities. In this study, we focus on the homologous loop regions in human laminin alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
2
9
0
2
Order By: Relevance
“…Dystroglycan interacts with the LG4 regions of the α1, α2 and α5 chains ) and the binding sites for heparin and dystroglycan overlap in the α1LG4 module (Andac et al 1999). Further complexity has been shown by Yokoyama et al (2005). Fibroblasts spread well on the α1LG4 module but poorly on the homologous modules of α2, α3 and α4 chains.…”
Section: Lamininsmentioning
confidence: 95%
“…Dystroglycan interacts with the LG4 regions of the α1, α2 and α5 chains ) and the binding sites for heparin and dystroglycan overlap in the α1LG4 module (Andac et al 1999). Further complexity has been shown by Yokoyama et al (2005). Fibroblasts spread well on the α1LG4 module but poorly on the homologous modules of α2, α3 and α4 chains.…”
Section: Lamininsmentioning
confidence: 95%
“…It is known that some membrane proteins are associated with integrins and regulate integrin functions. These include syndecans [Beauvais and Rapraeger, 2004;Yokoyama et al, 2005], tetraspanins [Berditchevski and Odintsova, 1999;Nishiuchi et al, 2005], and galectins [Woo et al, 1990;Hughes, 2001]. We found that b3SA has weak heparin-binding activity (data not shown).…”
Section: Discussionmentioning
confidence: 50%
“…In the case of syndecans, alternative promoting or inhibiting functions may depend upon their differential ability to serve as co-receptors with ligand specificities dictated by their GAG chain diversity [203,204]. This idea has its grounds in the fact that syndecan-1 has been reported to induce intracellular signal transduction independently of integrins [205] and that binding of a variety of tumor cell types to laminins requires a syndecan-1-substrate interaction [206][207][208][209]. A similar putative interaction Fig.…”
Section: Implication Of Pgs In the Optimization Of The Tumor Cells' Imentioning
confidence: 99%